2017
DOI: 10.3857/roj.2016.02019
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgical clips in the evaluation of interfractional uncertainty for treatment of hepatobiliary and pancreatic cancer with postoperative radiotherapy

Abstract: PurposeTo evaluate the utility of implanted surgical clips for detecting interfractional errors in the treatment of hepatobiliary and pancreatic cancer with postoperative radiotherapy (PORT).Methods and MaterialsTwenty patients had been treated with PORT for locally advanced hepatobiliary or pancreatic cancer, from November 2014 to April 2016. Patients underwent computed tomography simulation and were treated in expiratory breathing phase. During treatment, orthogonal kilovoltage (kV) imaging was taken twice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…With the development of radiotherapy techniques, 3D-CRT or IMRT has become widely used to treat abdominal malignancies, allowing optimal qualitative treatment with reduced toxicity [ 26 ]. In addition, Sun et al [ 27 ] conducted plan comparison between conformal radiotherapy and IMRT in the treatment of gallbladder cancer, and showed that IMRT reduced radiation dose to liver and right kidney, significantly.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of radiotherapy techniques, 3D-CRT or IMRT has become widely used to treat abdominal malignancies, allowing optimal qualitative treatment with reduced toxicity [ 26 ]. In addition, Sun et al [ 27 ] conducted plan comparison between conformal radiotherapy and IMRT in the treatment of gallbladder cancer, and showed that IMRT reduced radiation dose to liver and right kidney, significantly.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7,8 With recent advances in RT techniques, intensity-modulated RT (IMRT), stereotactic body RT (SBRT), and proton beam therapy (PBT) can deliver high doses to the tumor as well as minimizing the radiation dose to surrounding normal tissues. [9][10][11][12][13][14][15][16][17] Because of the apparent physical properties of proton beams that can deposit high doses of radiation to the target without an exit dose outside the target, PBT has been attracting attention. Conceptually, PBT has potential advantages of an accelerated RT, known as simultaneous integrated boost (SIB), which different doses can be delivered simultaneously to different targets.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the combinations of radiotherapy and chemotherapy in LAPC patients, its effects of local and distant tumor control as well as its tolerability might be important. Previous studies which treated LAPC patients with CRT using conventional RT reported 27%–77% of grade ≥3 toxicity and median OS duration of 8–12 months [ 3 , 4 , 6 - 11 , 19 , 20 ]. Recently, IMRT technique has been applied in LAPC patients to improve local tumor control by delivering the higher dose to tumor and to minimize potential of toxicity by reducing radiation to surrounding normal tissues, such as adjacent gastrointestinal structures, and several studies have shown lower rate (15%–24%) of grade ≥3 toxicity and promising median OS (12–15.3 months) [ 14 - 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%